Approaches and constraints to identification and quantitation of asbestos fibers - Langer, Arthur M. (1974)
Asbestos fibers, members of complex crystal–chemical systems, possess some range in characteristic properties. Identification of fibers requires morphological, structural, and chemical data. Most current work centers on identification of single, sublight-microscopic fibers present as contaminants in a range of media. Constraints encountered in the analysis of such materials are: sample preparation of the differing media; level of fiber exposure (contamination); presence (kind and amount) of other particles; tissue types and their different preparation techniques; homogeneity of samples and their preparations; use of proper instrumental technique; time required for analysis, and quantitation.